Pengaruh Disiplin Kerja Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pada PT. Fajar Mitra Krida Abadi Bogor - Viola Nur Fatari; Retno Japanis Permatasari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the effect of work discipline and physical work environment on employee performance at PT Fajar Mitra Krida Abadi Bogor. This research uses a quantitative method with an associative approach. The population of this study consists of all employees of PT Fajar Mitra Krida Abadi Bogor totaling 52 respondents, and the sampling technique applied is census sampling. Data were collected through questionnaires that had been tested for validity and reliability. The data analysis techniques used include classical assumption tests, multiple linear regression analysis, partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test), and coefficient of determination analysis. The results of the t-test show that work discipline has a positive and significant effect on employee performance, with a t-value of 3.521, which is greater than the t-table value of 2.009, and a significance value of less than 0.05. The physical work environment also has a positive and significant effect on employee performance, with a t-value of 5.896, which is greater than the t-table value of 2.009, and a significance value below 0.05. Furthermore, the results of the F-test indicate that work discipline and physical work environment simultaneously have a significant effect on employee performance, with an F-value of 51.864, which is greater than the F-table value of 3.19, and a significance value of less than 0.05. The coefficient of determination (R Square) value of 0.679 indicates that 67.9% of the variation in employee performance can be explained by work discipline and physical work environment, while the remaining 32.1% is influenced by other factors not examined in this study. The findings of this research are expected to provide practical implications for company management in improving employee performance through strengthening work discipline and creating a supportive physical work environment